Two quantitative trait loci, Dw1 and Dw2, are primarily responsible for rootstock-induced dwarfing in apple. (11th February 2015) - Foster, Toshi M; Celton, Jean-Marc; Chagné, David; Tustin, D Stuart; Gardiner, Susan E
Abstract: The apple dwarfing rootstock 'Malling9' ('M9') has been used worldwide both to reduce scion vigour and as a genetic source for breeding new rootstocks. Progeny of 'M9' segregate for rootstock-induced dwarfing of the scion, indicating that this trait is controlled by one or more genetic factors. A quantitative trait locus (QTL) analysis of a rootstock population derived from the cross between 'M9' × 'Robusta5' (non-dwarfing) and grafted with 'Braeburn' scions identified a major QTL ( Dw1 ) on linkage group (LG) 5, which exhibits a significant influence on dwarfing of the scion. A smaller-effect QTL affecting dwarfing ( Dw2 ) was identified on LG11, and four minor-effect QTLs were found on LG6, LG9, LG10 and LG12. Phenotypic analysis indicates that the combination of Dw1 and Dw2 has the strongest influence on rootstock-induced dwarfing, and that Dw1 has a stronger effect than Dw2 . Genetic markers linked to Dw1 and Dw2 were screened over 41 rootstock accessions that confer a range of effects on scion growth. The majority of the dwarfing and semi-dwarfing rootstock accessions screened carried marker alleles linked to Dw1 and Dw2 . This suggests that most apple dwarfing rootstocks have been derived from the same genetic source. Abstract : Fruit crops: Determining dwarfism in apples Dwarfing revolutionized apple cultivation, but its genetic basis is poorly understood. Researchers led by Toshi Foster at the New Zealand Institute for Plant and Food Research have now analysed the basis of dwarfing and discovered two interacting genetic regions account for the reduced growth produced by most 'dwarfing' apple rootstocks. To distinguish genetic from environmental effects, the team analysed a large, standardized population of apple trees grown on both dwarfing and more vigorous rootstocks. Their results confirmed one previously identified dwarfing gene, Dw1, and uncovered a second, Dw2 . Unlike Dw1, Dw2 alone does not cause dwarfing, suggesting it may act as an enhancer of Dw1 . Foster's team found markers of Dw1 and Dw2 in most modern dwarfing apple rootstocks, implying all such rootstocks derive from a single origin. The study provides crucial information for future apple rootstock breeding.